Application of Acupressure Therapy on Normal Post Partum with Nursing Problems Breastfeeding is not Effective - Nadi Aprilyadi; Yeni Elviani; Eka Apriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Based on a survey in Indonesia, 38% of mothers stopped breastfeeding because of problems with ineffective breastfeeding. The application of acupressure therapy to normal post partum mothers with ineffective breastfeeding nursing problems in the Independent Practice Midwife of Lubuklinggau City in 2022. The purpose of this research is to find out the results of applying acupressure therapy to overcome the problem. breastfeeding is not effective in normal postpartum mothers. The research method applied by the researcher is descriptive research using a case study approach, case study is research by examining a problem through a case consisting of a single unit which means that one person or a group has problems. The subjects in this study were two postpartum maternal clients with a history of normal delivery who met the inclusion criteria. In this study, the data collection method used was to perform acupressure therapy on Normal Post Partum mothers with ineffective breastfeeding problems. In this study, for nursing interventions that were not effective, the application of Acupressure Therapy was carried out.